2020
DOI: 10.3390/ijms21186660
|View full text |Cite
|
Sign up to set email alerts
|

The brlA Gene Deletion Reveals That Patulin Biosynthesis Is Not Related to Conidiation in Penicillium expansum

Abstract: Dissemination and survival of ascomycetes is through asexual spores. The brlA gene encodes a C2H2-type zinc-finger transcription factor, which is essential for asexual development. Penicillium expansum causes blue mold disease and is the main source of patulin, a mycotoxin that contaminates apple-based food. A P. expansum PeΔbrlA deficient strain was generated by homologous recombination. In vivo, suppression of brlA completely blocked the development of conidiophores that takes place after the formation of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…A recent study in P. expansum showed that the brlA gene not only affects the stage of conidiation of the fungus but also affects the biosynthesis of secondary metabolites. Zetina-Serrano et al [ 157 ] showed that the suppression of brlA results in a strain devoid of conidia and that the production of communesins and derivatives was drastically decreased, whereas the production of chaetoglobosins and derivatives increased. Neither patulin nor citrinin production was affected by the suppression of brlA .…”
Section: Regulation Of Secondary Metabolismmentioning
confidence: 99%
“…A recent study in P. expansum showed that the brlA gene not only affects the stage of conidiation of the fungus but also affects the biosynthesis of secondary metabolites. Zetina-Serrano et al [ 157 ] showed that the suppression of brlA results in a strain devoid of conidia and that the production of communesins and derivatives was drastically decreased, whereas the production of chaetoglobosins and derivatives increased. Neither patulin nor citrinin production was affected by the suppression of brlA .…”
Section: Regulation Of Secondary Metabolismmentioning
confidence: 99%
“…The brlA gene, which encodes the C 2 H 2 zinc-finger transcription factor, modulates conidiation-specific genes and initiates conidiation; abaA activated by BrlA is required for the differentiation and function maintenance of phialides, and wetA activated by AbaA is essential for spore formation and maturation [ 37 ]. A recent study demonstrated the conserved role of BrlA in the conidiophore development of P. expansum [ 38 ]. These findings further support that PeRmtC positively regulates conidiogenesis of P. expansum by mediating the two important regulatory genes PeBrlA and PeAbaA .…”
Section: Discussionmentioning
confidence: 99%